The Analysis of Midwife Workload as an Effort to Improve Performance and Service Quality - Sherly Jeniawaty; Queen Khoirun Nisa Mairo (Aloha International Journal of Health Advancement (AIJHA), 2018)
Background: Results of preliminary studies conducted at the Puskesmas Hospitalization in the city of Surabaya regarding duties and responsibilities as a midwife, showed that midwives had overlapping duties and responsibilities because midwives not only handled maternal and child problems as their main duties and functions, but midwives also carried out all activities. The Puskesmas in its working area includes 6 basic six primary health centers, namely prevention and control of diseases, health promotion, MCH and family planning services, environmental health, nutrition improvement, and basic treatment and services. In addition, midwives also carry out other administrative activities such as joining the kecamatan and kelurahan PKK driving teams, and becoming treasurers of the National Health Insurance (JKN). This is due to the limited personnel owned by the Puskesmas so that it can affect the workload of midwives, because in addition to exercising their authority the midwife also carries out other tasks. Based on the above problems, and remembering the duties and functions of midwives as maternal and child health providers, it is important to conduct research on midwife workload analysis in carrying out their authority in the working area of Surabaya Inpatient Health Centers. Method: This study has a cross sectional quantitative research design. In this study using 2 variables (exogenous), namely Midwife Work Performance and Midwife Performance or Productivity. In this study the endogenous variables are the quality of midwife services in the Surabaya Inpatient Health Center. The population used in this study were all implementing midwives, who provided services in 10 inpatient health centers in Surabaya. Results and Analysis: Pearson correlation test results indicate there is a significant relationship between workload and performance (p = 0.000) and there is a significant relationship between workload and service quality (p = 0.000). Discussion and Conclusion: in order to avoid work fatigue, it is necessary to rearrange work shifts in accordance with the rules and conditions of work shift provisions in maternity inpatient units, the determination of clear rest hours, when service hours can be accompanied by work music, and additional labor reduce workload, as well as the division of workload according to ability, and routinely carry out refreshing to reduce saturation. Keywords: Workload, Performance, Service quality